AGILE Highlights after Six Years in Orbit - Carlotta Pittori (Acta Polytechnica CTU Proceedings)
AGILE is an ASI space mission in collaboration with INAF, INFN and CIFS, dedicated to the observation of the gamma-ray Universe in the 30 MeV - 50 GeV energy range, with simultaneous X-ray imaging capability in the 18-60 keV band. The AGILE satellite was launched on April 23rd, 2007, and produced several important scientic results, among which the unexpected discovery of strong ares from the Crab Nebula. This discovery won to the AGILE PI and the AGILE Team the Bruno Rossi Prize for 2012 by the High Energy Astrophysics division of the American Astronomical Society. Thanks to its sky monitoring capability and fast ground segment alert system, AGILE detected many Galactic and extragalactic sources: among other results AGILE discovered gamma-ray emission from the microquasar Cygnus X-3, detected many bright blazars, discovered several new gamma-ray pulsars, and discovered emission up to 100 MeV from Terrestrial Gamma-Ray Flashes. We present an overview of the main AGILE Data Center activities and the AGILE scientic highlights after 6 years of operations.